Comparison of pollinators and natural enemies: a meta‐analysis of landscape and local effects on abundance and richness in crops. (12th April 2013) - Shackelford, Gorm; Steward, Peter R.; Benton, Tim G.; Kunin, William E.; Potts, Simon G.; Biesmeijer, Jacobus C.; Sait, Steven M.
ABSTRACT: To manage agroecosystems for multiple ecosystem services, we need to know whether the management of one service has positive, negative, or no effects on other services. We do not yet have data on the interactions between pollination and pest‐control services. However, we do have data on the distributions of pollinators and natural enemies in agroecosystems. Therefore, we compared these two groups of ecosystem service providers, to see if the management of farms and agricultural landscapes might have similar effects on the abundance and richness of both. In a meta‐analysis, we compared 46 studies that sampled bees, predatory beetles, parasitic wasps, and spiders in fields, orchards, or vineyards of food crops. These studies used the proximity or proportion of non‐crop or natural habitats in the landscapes surrounding these crops (a measure of landscape complexity), or the proximity or diversity of non‐crop plants in the margins of these crops (a measure of local complexity), to explain the abundance or richness of these beneficial arthropods. Compositional complexity at both landscape and local scales had positive effects on both pollinators and natural enemies, but different effects on different taxa. Effects on bees and spiders were significantly positive, but effects on parasitoids and predatory beetles (mostly Carabidae and Staphylinidae) were inconclusive. Landscape complexity had significantly stronger effects on bees than it did on predatory beetles and significantly stronger effects in non‐woody rather than in woody crops. Effects on richness were significantly stronger than effects on abundance, but possibly only for spiders. This abundance‐richness difference might be caused by differences between generalists and specialists, or between arthropods that depend on non‐crop habitats (ecotone species and dispersers) and those that do not (cultural species). We call this the 'specialist‐generalist' or 'cultural difference' mechanism. If complexity has stronger effects on richness than abundance, it might have stronger effects on the stability than the magnitude of these arthropod‐mediated ecosystem services. We conclude that some pollinators and natural enemies seem to have compatible responses to complexity, and it might be possible to manage agroecosystems for the benefit of both. However, too few studies have compared the two, and so we cannot yet conclude that there are no negative interactions between pollinators and natural enemies, and no trade‐offs between pollination and pest‐control services. Therefore, we suggest a framework for future research to bridge these gaps in our knowledge.